Endoscopic or surgical treatment for necrotizing pancreatitis: Comprehensive systematic review and meta-analysis - Mohamadnejad, Mehdi; Anushiravani, Amir; Kasaeian, Amir; Sorouri, Majid; Djalalinia, Shirin; Kazemzadeh Houjaghan, Amirmasoud; Gaidhane, Monica; Kahaleh, Michel (Endoscopy International Open, 2022)
Background and study aims Treatment of necrotizing pancreatitis is changed over the past two decades with the availability of endoscopic, and minimally invasive surgical approaches. The aim of this systematic review was to assess outcomes of endoscopic drainage, and different types of surgical drainage approaches in necrotizing pancreatitis. Methods Medline, Embase, Scopus, and Web of Science were searched from 1998 to 2020 to assess outcomes in endoscopic drainage and various surgical drainage procedures. The assessed variables consisted of mortality, development of pancreatic or enteric fistula, new onset diabetes mellitus, and exocrine pancreatic insufficiency.Results One hundred seventy studies comprising 11,807 patients were included in the final analysis. The pooled mortality rate was 22 % (95 % confidence interval [CI]: 19%–26 %) in the open surgery (OS), 8 % (95 %CI:5 %–11 %) in minimally invasive surgery (MIS), 13 % (95 %CI: 9 %–18 %) in step-up approach, and 3 % (95 %CI:2 %–4 %) in the endoscopic drainage (ED). The pooled rate of fistula formation was 35 % (95 %CI:28 %–41 %) in the OS, 17 % (95 %CI: 12%–23 %) in MIS, 17 % (95 %CI: 9 %–27 %) in step-up approach, and 2 % (95 %CI: 0 %–4 %) in ED. There were 17 comparative studies comparing various surgical drainage methods with ED. The mortality rate was significantly lower in ED compared to OS (risk ratio [RR]: 30; 95 %CI: 0.20–0.45), and compared to MIS (RR: 0.40; 95 %CI: 0.26–0.6). Also, the rate of fistula formation was lower in ED compared to all other surgical drainage approaches. Conclusions This systematic review demonstrated lower rate of fistula formation with ED compared to various surgical drainage methods. A lower rate of mortality with ED was also observed in observational studies. PROSPERO Identifier: CRD42020139354